Sinergisitas Peran dan Fungsi LPPM Tridarma Perguruan Tinggi dalam Optimalisasi Kampus Merdeka - Eli Masnawati; Eli Retnowati; Rahayu Mardikaningsih (Departement of Mathematics Education, 2023)
Higher education tridarma activities in the independent campus curriculum really need the role and function of research and community service. The synergy of the use of research and dedication to seek and find solutions in society for some of the problems that will be found solutions depart from research that will be implemented in the form of synergy of the independent campus curriculum. The Synergy of the Roles and Functions of the Higher Education Tridarma Institute in Optimizing the Independent Campus (1) The Role of the LPPM STKIP PGRI Bangkalan. (2) Functions of LPPM STKIP PGRI Bangkalan. (3) Research synergy and community service in Optimizing the Independent Campus. (4) Products of LPPM STKIP PGRI Bangkalan. This type of research is descriptive qualitative research, uncovering the phenomenon of problems from informants and informants. Data Source STKIP Chairperson, Vice Chairmen 1, 2 and 3, lecturers, education staff, several foundation management figures. Data was collected by interview, observation and documentation methods. Data analysis was performed using qualitative data analysis procedures. The results of the study show (1) The role of LPPM STKIP PGRI Bangkalan in Optimizing the Merdeka Campus has not been able to play an optimal role. (2) The function of LPPM has not fully functioned according to its duties in its role in synergizing research and independent campus service. (3) Research synergy and community service in carrying out the Independent Campus Tridarma have not synergized and have not been implemented (4) LPPM STKIP PGRI Bangkalan Independent Campus products are only implementation (KKN) Real work lectures, conducting several training methods for writing scientific journals, publishing HKI and managing Labs Language.